Analisis Pemberitaan Banjir Lahar Dingin di Sumatera Barat dalam Media Detik.com dan Antaranwes.com - Assaudi, Budi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
News related to the cold lava flood disaster in West Sumatra that was broadcasted in print, electronic and online media became public consumption, causing perceptions in the community. Online media both Antaranews.com and Detik.com have news related to cold lava floods in West Sumatra. The media provided information from different perspectives in presenting the news. The floods came from material from Mount Marapi that erupted some time ago, most of which was on the slopes of the mountain. The material was washed away by rainwater downstream. Meanwhile, Antaranews.com provides information to the public by quoting the statement of Andalas University researchers that the accumulation of fallen tree material in the upper reaches of the Batang Anai river became a natural dam, due to the volcanic eruption of Mount Marapi accompanied by high rainfall as the cause of the collapse of natural dams and resulting floods. Framing analysis is viewed from syntactic, thematic, script and rhetorical structures. This research uses a qualitative approach with the theory of Zhongdang Pan and M. Kosicki. The results prove that the two online media have different points of view and news packaging, each emphasizing based on the data and facts received. After analyzing the two news articles, the researcher concluded that both news articles provided information on the causes of the flood disaster in West Sumatra. However, if seen in the Detik.com online media, the floods were caused by moderate to heavy rains that washed away volcanic material from the eruption of Mount Marapi in the form of cold lava. Another case with the information put forward by the Antaranews.com media that the flood was caused by the collapse of a natural dam in the upstream section of the Batang Anai river due to the vibration of the volcanic earthquake of Mount Marapi accompanied by high rainfall.